2003
DOI: 10.1182/blood-2002-08-2502
|View full text |Cite
|
Sign up to set email alerts
|

Primary immune responses to human CMV: a critical role for IFN-γ–producing CD4+ T cells in protection against CMV disease

Abstract: The correlates of protective immunity to disease-inducing viruses in humans remain to be elucidated. We determined the kinetics and characteristics of cytomegalovirus (CMV)-specific CD4 ؉ and CD8 ؉ T cells in the course of primary CMV infection in asymptomatic and symptomatic recipients of renal transplants. Specific CD8 ؉ cytotoxic T lymphocyte (CTL) and antibody responses developed regardless of clinical signs. CD45RA ؊ CD27 ؉ CCR7 ؊ CTLs, although classified as immature effector cells in HIV infection, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
338
4
3

Year Published

2004
2004
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 383 publications
(370 citation statements)
references
References 49 publications
25
338
4
3
Order By: Relevance
“…Likewise, loss of CD27 is a very late event occurring on CMV-specific T cells after primary infection [37]. To analyze modulation of CD27 expression on antigen-specific T cells after stimulation in vivo, primary and secondary influenza A virus infections were performed.…”
Section: Cd27 Expression Is Lost After Repetitive Stimulation In Vivomentioning
confidence: 99%
“…Likewise, loss of CD27 is a very late event occurring on CMV-specific T cells after primary infection [37]. To analyze modulation of CD27 expression on antigen-specific T cells after stimulation in vivo, primary and secondary influenza A virus infections were performed.…”
Section: Cd27 Expression Is Lost After Repetitive Stimulation In Vivomentioning
confidence: 99%
“…22,23 Effective immune responses have been shown to depend on both CD4 + and CD8 + T lymphocytes. 24,25 In the absence of CD4 helper cells, CTLs were less protective against challenge with a pathogen. Furthermore, helper T lymphocytes have been found to be important for the development of T-cell memory.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of virusspecific T cells during acute infections with EBV, HIV, or CMV revealed that early effector T cells are clearly distinct from the effector-type CD45RA ϩ CD27 Ϫ T cells found in latently infected persons. T cells expanding early in immune responses have CD45R0, CD28, CD27 surface expression, express the G 1 phaseassociated nuclear Ag Ki-67, and contain perforin and granzyme B (12)(13)(14). These observations raised questions about the generation of CD45RA ϩ CD27 Ϫ T cells and their role in protective immunity (10).…”
mentioning
confidence: 99%